Numerical and experimental characterization of a button-shaped miniaturized UHF antenna on magneto-dielectric substrate. Issue 3 (2nd May 2013) - Aldrigo, Martino; Costanzo, Alessandra; Masotti, Diego; Baldisserri, Carlo; Dumitru, Ioan; Galassi, Carmen
Abstract : The design and characterization of a new broadband small patch antenna, based on an innovative magneto-dielectric material and suitable for wearable applications at 868 MHz, is presented. To reduce antenna dimensions, while preserving its radiation and matching performance, a barium-strontium hexaferrite Ba0.75 Sr0.25 Fe12 O19 has been synthesized as the antenna substrate to achieve magnetic permeability double than vacuum in the band of interest. First material realization is characterized and dispersive permittivity and permeability behaviors are included in the design of a small patch antenna with a shorting-plate. A button-size realization is obtained and its suitability for wearable applications is numerically and experimentally demonstrated on body with and without the presence of conductive shielding. Very good agreement with measurements is demonstrated for both matching and radiation performance of the antenna.